The Theatre of Justice : Aspects of Performance in Greco-Roman Oratory and Rhetoric - BRILL (Mnemosyne, Supplements Ser, 2017)
Intro -- ‎Contents -- ‎Acknowledgements -- ‎Notes on Contributors -- ‎Chapter 1. Introduction (Papaioannou, Serafim and da Vela) -- ‎Part 1. Speakers-Audience -- ‎Chapter 2. Audience Reaction, Performance and the Exploitation of Delivery in the Courts and Assembly (Worthington) -- ‎Chapter 3. 'Conventions' in/as Performance: Addressing the Audience in Selected Public Speeches of Demosthenes (Serafim) -- ‎Chapter 4. Would I Lie to You? Narrative and Performance in Isaios 6 (Griffith-Williams) -- ‎Chapter 5. The Orator and the Ghosts: Performing the Past in Fourth-Century Athens (Westwood) -- ‎Chapter 6. Speech without Limits: Defining Informality in Republican Oratory (Steel) -- ‎Part 2. Ethopoiia -- ‎Chapter 7. Ēthos and Logical Argument in Thucydides' Assembly Debates (Kremmydas) -- ‎Chapter 8. Elite Rhetoric and Self-Presentation: Metellus Numidicus Returns (van der Blom) -- ‎Part 3. Hypocrisis-Delivery-Actio -- ‎Chapter 9. Pitiable Dramas on the Podium of the Athenian Law Courts (Apostolakis) -- ‎Chapter 10. From the Stage to the Court: Rhetorical and Dramatic Performance in Donatus' Commentary on Terence (da Vela) -- ‎Chapter 11. Oratorical Performance in Pliny's Letters (Tempest) -- ‎Part 4. Emotions in the Law-Court -- ‎Chapter 12. The Mind's Theatre: Envy, Hybris and Enargeia in Demosthenes' Against Meidias (Spatharas) -- ‎Chapter 13. How to "Act" in an Athenian Court: Emotions and Forensic Performance (Harris) -- ‎Chapter 14. Roman Judges and Their Participation in the "Theatre of Justice" (Hall) -- ‎Part 5. Language and Style in Performance -- ‎Chapter 15. Style, Persona and Performance in Aeschines' Prosecution of Timarchus (Carey) -- ‎Chapter 16. Narrative and Performance in the Speeches of Apollodoros (Kapparis) -- ‎Chapter 17. Public Performance and the Language of Antiphon's Speeches (Vatri) -- ‎Bibliography -- ‎Index Locorum.